2019
DOI: 10.21608/eajbsa.2019.58298
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Different Traps for Monitoring Sucking and Chewing Insect Pests of Crops

Abstract: Entomology Journal publishes original research papers and reviews from any entomological discipline or from directly allied fields in ecology, behavioral biology, Various type of sticky traps is frequently used for monitoring the sucking pests like jassid, aphid, whitefly, and thrips. Light traps and pheromones traps are species specific and commonly used for capturing the moths such as Spodoptera litura, Helicoverpa armigera and Leucinodes orbonalis. The sucking and chewing are very destructive pests of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…Navasero (2019) and Ramzan et al (2021 b ) had reported similar findings of adult body length and wing expanse. The different management practices such as monitoring, cultural, physical, chemical, biological and entomopathogenic fungi have been recommended by many experts (Murtaza et al, 2019;Ramzan et al, 2021 a,b ) in the country which can be tested to control this noxious pest of agricultural crops in Pakistan (Ramzan et al, 2020). The pheromones trap as well as monitoring is the best way to control this destructive and emerging pest in the study area.…”
Section: Resultsmentioning
confidence: 99%
“…Navasero (2019) and Ramzan et al (2021 b ) had reported similar findings of adult body length and wing expanse. The different management practices such as monitoring, cultural, physical, chemical, biological and entomopathogenic fungi have been recommended by many experts (Murtaza et al, 2019;Ramzan et al, 2021 a,b ) in the country which can be tested to control this noxious pest of agricultural crops in Pakistan (Ramzan et al, 2020). The pheromones trap as well as monitoring is the best way to control this destructive and emerging pest in the study area.…”
Section: Resultsmentioning
confidence: 99%
“…Many scientists have reported more than 70 number of insect species on brinjal (Borkakati et al, 2019). Different control measures (cultural, physical, mechanical, biological, botanicals, entomopathogenic fungi and chemicals) had been adopted by national and international scale to control pest population under laboratory as well as field conditions Murtaza et al, 2019). Each and every control measure has its own advantage and disadvantage.…”
Section: Resultsmentioning
confidence: 99%
“…However, the chemical method has proved harmful for many non-targeted fauna (Hassan et al, 2007), in addition to its negative impact on the environment (Malik et al, 2015). Furthermore, the intensive application of the same group of insecticides against the target pest can enhance the development of resistance to the chemicals used (Murtaza et al, 2019;Rajput, 2004).…”
Section: Introductionmentioning
confidence: 99%